A systemic review of the utility of antituberculosis therapy for presumed tuberculous uveitis - Jemma W. Taylor; Ginevra E. L. Wright; Lyndell L. Lim; Justin T. Denholm (BMC Infectious Diseases)
Abstract Background Uveitis presumed to be secondary to Mycobacterium tuberculosis is a rare but potentially blinding condition. Difficulty in making an accurate diagnosis and the low incidence of TB uveitis (TBU) contribute to the lack of evidence regarding the best management of this condition. This systematic review aims to analyse existing research to provide a summary of the literature regarding the utility of TB therapy for the management of TBU. Methods This systematic review was prospectively registered on PROSPERO (PROSPERO 2021 CRD42021273379). We searched Medline, Embase and Central databases, and the search was done on 20th June 2023 with an updated literature search. Results We included 55 studies and found that the heterogeneity in the methodology of these studies precluded metanalysis, and a narrative analysis was undertaken. Risk of bias analysis was undertaken using the Newcastle–Ottawa scale. Conclusions Key findings of this systematic review include multiple systemic biases in the available evidence, and general lack of control for confounding variables. This results in many unanswered questions regarding the utility of TB therapy for TBU and reinforces the need for more data in this area.